(3LhGgQ GdHMGQs - (3eLghds ((3bVGA bdYI SdWGfjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj SdWGfg fYJ GdCRd, GdeGLO GdaQO GdPj ZaQGfg jeMh GdRdd, QH JYGdi TCfg eSJhLH ZaQGfg dG jfHZj QVhGfg EdG HENdGU GdYeds
(3BNQgG (B:s
(3ajUHM bO RGd Yfg GdScQ hjTQH HYO GdUHM ajUHMhG EPG LGA hbJ GdXgQ Edi Cf GJNP YJHGf Hf eGdc UfjYG Cj VjGaI hOYG QLGdG ef GdeSdejfs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs